Evaluation of uniformity, variability, and stability of agronomic traits of doubledd haploid rice lines resulting from anther culture - PRIATNA SASMITA (Smujo International, 2010)
Abstract. Sasmita P. 2010. Evaluation of uniformity, variability, and stability of agronomic traits of doubled haploid rice lines resulting from anther culture. Nusantara Bioscience 2: 67-72. The formation of doubled haploid lines in anther culture aims to accelerate the acquisition of pure lines. Selection of the desired traits can be done directly to the progeny of anther culture results at early generations. This experiment aims to determine agronomic traits, uniformity, and stability of the doubled haploid lines, and obtain the putative doubled haploid lines as the material for further evaluation to obtain expected lines. The first experiments used completely randomized design which was repeated five times. The treatments were 111 doubled haploid lines of first generation of anther culture results (DH1). The second experiment used split-plot design with the main plot treatments were doubled haploid lines resulting from anther culture and the subplot treatment was the second generation of doubled haploid lines (DH2) until the fifth generation (DH5). The results show that each plant within the same line have uniform agronomic traits, while the plants between different lines have different agronomic traits. The results of further evaluation on three out of 111 doubled haploid lines derived from the second to fifth generations show no difference between generations for each trait of the same lines. The results also show that the agronomic traits of the doubled haploid line were stable from generation to generation.